Disguised Blessings amid Covid‑19: Opportunities and Challenges for South African University Students with Learning Disabilities (Journal of Student Affairs in Africa, 2021)
The Covid‑19 pandemic has led to changes from traditional face-to-face teaching and learning to online systems. These changes have resulted in a concerted focus by local and international scholars on how some students are disadvantaged from accessing pedagogy due to a lack of resources and supportive living conditions that enable meaningful off‑campus learning. Simultaneously, disabilities in higher education is getting international attention, too, highlighting how students with disabilities are vulnerable to further exclusions and mental health problems. This article focuses on the pedagogical arrangements during the Covid‑19 pandemic and the challenges and opportunities associated with online and remote learning for university students with learning disabilities. The article draws on the narratives of fifteen students with learning disabilities from a university in South Africa. An analysis of students’ narratives within the Capability Approach’s concept of conversion factors revealed how circumstances could enable or constrain students’ abilities to achieve what they value in higher education. Students’ narratives show that they engage better with online and remote learning despite some notable challenges. In conclusion, the pedagogical arrangements aimed at alleviating the disruptions caused by the Covid‑19 pandemic can address the unmet educational needs of students with learning disabilities even though they have to overcome specific barriers.
Keywords: Capability Approach; conversion factors; Covid‑19; learning disabilities; online learning; student affairs; university students with special needs